Politics and society during the early medieval period / edited by K. A. Nizami - "Habib, Mohammad" (New Delhi, 1981)
The present volume deals with the political history of medieval India and covers important events and personalities from the Arab conquest of sind to the middle of fourteenth century. It contains India and provides a fresh perspective for the study of the altitude and achievements of the medieval Sultans.
Keywords: Political Science